Research potential and mechanism of rare earth elements promoting cadmium remediation efficiency in hyperaccumulator plants - Shi, An; Yang, Wenhao; Wang, Beibei; Zhang, Wen (Frontiers in Plant Science, 2026)
Cadmium (Cd) contamination poses serious ecological and health risks, and although hyperaccumulator plants offer a sustainable phytoremediation strategy, their field performance is often constrained by low biomass and limited tolerance under metal stress. Recent studies indicate that rare earth elements (REEs), especially lanthanum (La³+) and cerium (Ce³+), can influence multiple plant and soil processes that are relevant to Cd phytoextraction. Low-dose REEs have been reported to stimulate plant growth, modulate phytohormone signaling, enhance root development, and support antioxidant responses, which may collectively improve Cd tolerance and uptake. REEs can also modify soil chemical conditions and shape rhizosphere microbial communities that contribute to Cd mobilization. In some model species, REE exposure has been associated with the induction of systemic endocytosis, a process that may provide an additional pathway for the uptake of external ions, including Cd. Here, we synthesize current evidence on how REEs interact with plant physiological processes, soil Cd speciation, and rhizosphere microbial function, and we summarize emerging insights into REE-induced systemic endocytosis. We further propose a conceptual REE–plant–soil–microbe interaction framework to integrate these regulatory pathways. Finally, we discuss key uncertainties and research needs related to mechanism verification, ecological safety, and field applicability. This review provides a foundation for evaluating the potential of REEs as regulatory agents to enhance Cd phytoremediation using hyperaccumulator plants.